A 72-year-old male with recurrent syncope. Issue 10 (21st December 2016) - Perera, Dhanuka; Uppal, Rakesh; Hogan, John
Abstract : Clinical introduction: A 72-year-old patient presented with recurrent syncope 1 year after a myocardial infarction. Two recent falls resulted in fractures to the femur. Serial troponins were negative and ECG demonstrated fixed inferior ST-segment elevation and pathological Q waves. A Holter monitor recorded non-sustained ventricular tachycardia. A subsequent echocardiogram was abnormal, and further investigation with a three-dimensional (3D) cardiac CT coronary angiogram was performed (figure 1 ). Question: What is the most likely diagnosis? Cardiac tumour Hypertrophic obstructive cardiomyopathy Ventricular aneurysm Ventricular diverticulum